The impact of aging and hand dominance on the passive wrist stiffness of squash players: Pilot study - Hamilton, T.; Durand, S.; Igo Krebs, H. (JMIR Biomedical Engineering, 2019)
Background: Passive joint stiffness can influence the risk of injury and the ability to participate in sports and activities of daily living. However, little is known about how passive joint stiffness changes over time with intensive repetitive exercise, particularly when performing unilateral activities using the dominant upper limb.